A new immunochemical strategy for triple-negative breast cancer therapy - Chih-Wei Lin (Nature Portfolio, 2021)
Abstract Triple-negative breast cancer (TNBC) is a highly diverse group of malignant neoplasms which tend to have poor outcomes, and the development of new targets and strategies to treat these cancers is sorely needed. Antibody–drug conjugate (ADC) therapy has been shown to be a promising targeted therapy for treating many cancers, but has only rarely been tried in patients with TNBC. A major reason the efficacy of ADC therapy in the setting of TNBC has not been more fully investigated is the lack of appropriate target molecules. In this work we were able to identify an effective TNBC target for use in immunotherapy. We were guided by our previous observation that in some breast cancer patients the protein tropomyosin receptor kinase B cell surface protein (TrkB) had become immunogenic, suggesting that it was somehow sufficiently chemically different enough (presumably by mutation) to escaped immune tolerance. We postulated that this difference might well offer a means for selective targeting by antibodies. We engineered site-specific ADCs using a dual variable domain (DVD) format which combines anti-TrkB antibody with the h38C2 catalytic antibody. This format enables rapid, one-step, and homogeneous conjugation of β-lactam-derivatized drugs. Following conjugation to β-lactam-derivatized monomethyl auristatin F, the TrkB-targeting DVD-ADCs showed potency against multiple breast cancer cell lines, including TNBC cell lines. In addition, our isolation of antibody that specifically recognized the breast cancer-associated mutant form of TrkB, but not the wild type TrkB, indicates the possibility of further refining the selectivity of anti-TrkB DVD-ADCs, which should enhance their therapeutic index. These results confirmed our supposition that TrkB is a potential target for immunotherapy for TNBC, as well as for other cancers with mutated cell surface proteins.